Analisis Kecerdasan Emosional pada Peserta Didik Kelas VIII SMP Negeri 4 Pontianak - Nyami Yati; Luhur Wicaksono; Yuline Yuline (Departement of Mathematics Education, 2024)
This research discusses the emotional intelligence of Class VIII Students at Pontianak State Middle School. The problem in this research is which aspect of emotional intelligence is most dominant in students, what factors influence students, and what are the negative impacts of low emotional intelligence. The aim of this research is to describe and describe the characteristics of emotional intelligence of students at school, to find out aspects of emotional intelligence in students, to find out the factors that influence students, and to find out the negative impact of low emotional intelligence in students. The method used in this research is a descriptive method, while the type of research is a survey. The sample in this study amounted to 64 students. This study uses a quantitative approach. The technique used in this research is indirect communication technique, while the data collection tool uses a questionnaire.The results of this research show that the Emotional Intelligence of Class VIII Students at SMP Negeri 4 Pontianak is in the Fairly Good category with a percentage of 75%. Knowing yourself is in the Fairly Good category with a percentage of 66%. Managing emotions is in the Fairly Good category with a percentage of 62%. Self-motivation is in the Fairly Good category with a percentage of 75%. Recognizing other people's emotions is in the Fairly Good category with a percentage of 73%. Building relationships is in the Fairly Good category with a percentage of 68%.